Specific features of pharmacokinetics in children. (2nd January 2016) - Matalová, Petra; Urbánek, Karel; Anzenbacher, Pavel
Abstract: Human growth and development consist of a continuum of biological events. The impact of these developmental changes in drug disposition is largely related to changes in the body composition (e.g. body water content, plasma protein concentrations) and in the function of organs important in metabolism (e.g. the liver) and excretion (e.g. the kidney). The gastric emptying time during the neonatal period is prolonged, as well as intestinal motility. The ratio of body surface area to body weight is higher in children than in adults, which results in higher absorption of locally applied corticosteroids. Lower plasma protein levels and a higher body water content compared to adults may lead to diminished drug distribution. Phase I drug metabolizing system develops quickly and reaches adult levels between the third and sixth year of age. In newborns up to 3 months, the sulphotransferase activity is more developed than glucuronidation. Glomerular filtration, normalized to body surface area, approaches adult levels by 6 months of age. During the first decade of life, these changes are dynamic and can be non-linear and discordant, making standardized dosing inadequate. During rapid phases of growth/development, drug disposition and response may be altered. The main goal is to optimize drug therapy in children. This can be achieved through a fundamental understanding of how ontogeny influences pharmacokinetics.